How relevant is the individual’s levels of innovativeness in the investment decisions in equity crowdfunding campaigns? - Salvi, Antonio; Boscia, Vittorio; Nirino, Niccolò; Alam, Gazi Mahabubul; Petruzzella, Felice (Emerald Publishing, 2024)
Purpose: This study investigates the relationship between the individual’s levels of innovativeness (ILI) and the individual’s intention to finance (IIF) an equity crowdfunding campaign to understand whether and to what extent individuals' personalities (IP) can foster crowdfunding success. Design/methodology/approach: OLS models are applied based on survey data collected from 385 US and UK citizen respondents. Further, the baseline relationship between ILI and IIF is broken down on the basis of the interactions with two behavioral characteristics: proactive personality (PP) and openness to experience (OE). Findings: Results show a positive relationship between individual’s levels of innovativeness and the individual’s intention to finance an equity crowdfunding campaign. Furthermore, this relationship continues to be positive when moderators are introduced in the models, demonstrating that PP and OE are personal traits that strengthen the main relationship. Originality/value: Our findings contribute to enriching the stream of literature according to which equity crowdfunding is a helpful tool not only able to bridge the financial gap of companies during the first phase of their life cycle. The findings also contribute to the development of the innovation process, creating also a social identity within the crowdfunding community. © 2024, Emerald Publishing Limited.